An Analysis of Students’ Speaking Anxiety in Virtual Learning Classroom During the COVID-19 - Diana Fauzia Sari; Usman Kasim; Zakaria Zakaria; Yuliana Yuliana; Fenny Regita (English Education Journal, 2023)
This study aimed to find (1) the level of students’ speaking anxiety; and (2) factors causing the anxiety among students during virtual learning. This research used descriptive qualitative method, with the aim of analyzing data taken from 30 students of second semester students of English Education Department at Syiah Kuala University in academic year of 2021/2022. In conducting this study, the researcher used PSCAS (Public Speaking Class Anxiety Scale) questionnaire by Yaikhong and Usaha (2012). The results revealed that most of students (67%) were in medium  level which experienced by 20 out of 30 students. Meanwhile, the factors that most influenced student anxiety is lack of preparation factors (73%). Then, the next factors are grammatical error, motivation, friend/classmate, embarrassment, lack of confidence, fear of making mistakes, shyness and limited vocabulary. Based on these findings, it can be concluded that speaking in the virtual classroom can make students feel anxious and pressured. Anxiety can negatively affect students' speaking achievement; therefore, it is important for lecturers to be concerned with students' anxiety and find the best learning methods to reduce their anxiety, also by making the class atmosphere more comfortable and not monotonous.